Implementasi Kebijakan Keterwakilan Perempuan Dalam Pemilu Legislatif Kabupaten Subang - Kusumadewi, Rahayu; Wahidah, Idah; Julaeha, Wiwin (Department of Public Administration, 2018)
Fulfillment of women's political rights is a precondition for the realization of democratic representation which is balanced between men and women. The Regency of Subang is based on the results of the election in 2014, only a percentage of 16%. Therefore, this study aims to determine the implementation of the policy of women's representation in the General Election of Subang DPRD Members.This research uses qualitative method with descriptive approach. The data idan information obtained will be analyzed according to Miles and Huberman data analysis techniques consisting of data reduction activities, data presentation.The results showed that the fulfillment of women's representation in Subang Regency reached 41.74%, while the fulfillment of women's representation by the Gerindra Party reached 40.82% which showed that the policy of women's representation could be implemented well by the Gerindra Party because it was supported by communication, resources, dispositions and bureaucratic structure.The fulfillment obstacle arises both from internal party parties who have not been able to create an effective recruitment process or from women who are not ready to be involved in practical politics because the existing regeneration system has not been running systematically and sustainably. Meanwhile, to create quality control for women candidates, the Gerindra Party seeks to create a rigorous selection process through the stages of screening, screening, and verification